2021
DOI: 10.54279/mijeec.v3i1.245163
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly natural rubber latex and modified starch-based adhesive for wood-based panels application- A review

Abstract: The use of formaldehyde-based synthetic adhesives for the development of wood-based panels has increased rapidly in the industry. Synthetic adhesives are regarded as a threat to human health and a pollutant because they emit formaldehyde's carcinogenic gas. The breakthrough has prompted to seek for a long-term solution to the formaldehyde threat with natural resources. There has been a significant rise in bio-based adhesive technology and development in the wood-based panel industry. The current review article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…To enhance their strength, the natural rubber must be chemically modified or blended with synthetic resin. 34,35 This corroborates with current research, as it has been primarily shown that the properties of NRLbased adhesives can be improved by incorporating other bio-based polymers as fillers. For example, starch-reinforced NRL-based adhesives have been found to enhance the morphologies and mechanical properties of the overall adhesive system.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…To enhance their strength, the natural rubber must be chemically modified or blended with synthetic resin. 34,35 This corroborates with current research, as it has been primarily shown that the properties of NRLbased adhesives can be improved by incorporating other bio-based polymers as fillers. For example, starch-reinforced NRL-based adhesives have been found to enhance the morphologies and mechanical properties of the overall adhesive system.…”
Section: Introductionsupporting
confidence: 88%
“…Traditionally, solvent‐based adhesives have outperformed biobased adhesives, but they have done so at the expense of the users. To enhance their strength, the natural rubber must be chemically modified or blended with synthetic resin 34,35 . This corroborates with current research, as it has been primarily shown that the properties of NRL‐based adhesives can be improved by incorporating other bio‐based polymers as fillers.…”
Section: Introductionsupporting
confidence: 82%
“…Another plant-extracted material is natural rubber, a biopolymer of cis -1,4-polyisoprene with a mixture of proteins, carbohydrates, and lipids in an aqueous phase, from the tree Hevea braziliensis . It is an elastomeric biopolymer showing good flexibility, strength, and tack.…”
Section: Development Of Adhesives Based On Biosourcesmentioning
confidence: 99%
“…Another plant-extracted material is natural rubber, a biopolymer of cis -1,4-polyisoprene with a mixture of proteins, carbohydrates, and lipids in an aqueous phase, from the tree Hevea braziliensis . 74 It is an elastomeric biopolymer showing good flexibility, strength, and tack. However, it is difficult to bond with high-surface-energy materials requiring modification through epoxidation, 75 chlorination, 76 or grafting.…”
Section: Development Of Adhesives Based On Biosourcesmentioning
confidence: 99%
“…To meet the growing demand, much automated equipment is introduced in the panel production chain. At the raw material end, medium density man-made panels, high density man-made panels, and solid wood particle boards are commonly used as the main materials [ 4 ]. Inevitably, pits, bumps, oil spots, water spots, glue spots, chipped edges, bulging, and other problems are introduced in the processing process, which will directly affect the downstream surface lamination process.…”
Section: Introductionmentioning
confidence: 99%